2018
DOI: 10.1111/sode.12329
|View full text |Cite
|
Sign up to set email alerts
|

The key role of positive parenting and children’s temperament in post‐institutionalized children’s socio‐emotional adjustment after adoption placement. A RCT study

Abstract: Parenting interventions represent a means for experimentally inquiring socio‐emotional change of post‐institutionalized children after adoption. We used this approach in a three time point RCT study involving 83 post‐institutionalized children (Mage = 33.5 months, SD = 17.1) and their adoptive mothers (Mage = 42.6, SD = 3.9), attending either the Video‐Feedback Intervention to promote Positive Parenting in adoption and foster care or a dummy intervention. Controlling for gender and age at adoption, children sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
0
17
0
3
Order By: Relevance
“…Widespread overuse of attachment disorder diagnoses, as well as overuse of the term "attachment disorder" in the absence of diagnosis, have been documented (Allen & Schuengel, 2020;Woolgar & Baldock, 2015). For the vast majority of children with Reactive Attachment Disorder, symptoms disappear when placed in a stable caregiving environment that enables development of selective attachment relationships (Smyke et al, 2012), and which support caregivers' emotional availability (Barone et al, 2019). It should be noted that "attachment therapies" for attachment disorders are circulating, which are claimed to be effective but actually have no scientific evidence-base (Allen, 2018;Chaffin et al, 2006;Mercer, 2019).…”
Section: 35mentioning
confidence: 99%
“…Widespread overuse of attachment disorder diagnoses, as well as overuse of the term "attachment disorder" in the absence of diagnosis, have been documented (Allen & Schuengel, 2020;Woolgar & Baldock, 2015). For the vast majority of children with Reactive Attachment Disorder, symptoms disappear when placed in a stable caregiving environment that enables development of selective attachment relationships (Smyke et al, 2012), and which support caregivers' emotional availability (Barone et al, 2019). It should be noted that "attachment therapies" for attachment disorders are circulating, which are claimed to be effective but actually have no scientific evidence-base (Allen, 2018;Chaffin et al, 2006;Mercer, 2019).…”
Section: 35mentioning
confidence: 99%
“…In response to this need, a number of post-graduate training programs, as well as online training courses, have been developed, both in the U.S. and parts of Europe (e.g., Atkinson & Riley, 2017). Research into evidence-based adoption interventions is now ADOPTION IN THE SERVICE OF CHILD PROTECTION 38 underway (Barone et al, 2019;; Quality Improvement Center for Adoption and Guardianship Support and Preservation, 2019). Adoption continues to be an evolving area of child placement practice.…”
Section: Policy and Practice Implicationsmentioning
confidence: 99%
“…In the second study, Barone, Ozturk and Lionetti (2019) (n ¼ 83) found increased sensitivity among mothers in a six-month follow-up of the intervention group (b ¼ .83, p ¼ .001) which contributed to higher levels of emotional availability and decreased externalising behavioural problems among the children (b ¼ 0.55, p ¼ .001, b ¼ À2.64, p ¼ .01).…”
Section: Video-feedback Intervention To Promote Positive Parenting In Foster Care and Adoptionmentioning
confidence: 95%